ANALISIS HUBUNGAN FAKTOR KEINDAHAN, KENYAMANAN, KEAMANAN, TARIF, KERAMAHAN, KEUNIKAN DAN KEBERSIHAN TERHADAP TINGKAT KEPUASAN WISATAWAN BAHARI DI WILAYAH PESISIR PULAU KANIUNGAN KAMPUNG TELUK SUMBANG KECAMATAN BIDUK-BIDUK - Elki Pratama; Helminuddin; Erwiantono (2339-1324, 2020)
This study aimed to analyze the relationship between factors of beauty, comfort, safety, tariff, hospitality, uniqueness and cleanliness with satisfaction level of marine tourists and describe satisfaction level of marine tourists in coastal area of Kaniungan Island, Kampung Teluk Sumbang, Biduk-Biduk Sub-District. Sampling was conducted through accidental sampling technique with a sample size of 35 respondents. Furthermore, research data were analyzed using Likert Scale Method and Spearman’s Rank Correlation Coefficient. The results showed that: there was a relationship between factors of beauty, comfort, safety, tariff, hospitality, uniqueness and cleanliness with satisfaction level of marine tourists in coastal areas of Kaniungan Island, Kampung Teluk Sumbang, Biduk-Biduk Sub-District. Additionally, satisfaction level of marine tourists with factors of beauty, comfort, safety, tariff, hospitality, uniqueness and cleanliness was at a high level with ‘satisfied’ criteria. Keywords: Satisfaction, Marine Tourism, Kaniungan Island, Kampung Teluk Sumbang, Biduk - Biduk Sub-District